Effect of maternal food choices and pregnancy symptoms on birth outcomes - Aziz, Ainor Farahin (Universiti Sains Malaysia, 2012)
Maternal nutrition and pregnancy symptoms were shown to exert impacts on birth outcome. This cross-sectional study aimed to investigate the association of maternal food groups intake and pregnancy symptoms with birth outcome. A total of 99 pregnant women who were at their third trimester (32 to 40 gestational weeks) of gestation were recruited from Obstetrics and Gynaecology Clinic, two antenatal wards which were 2 Baiduri and 2 Akik of Hospital Universiti Sains Malaysia. Mothers were interviewed to complete the validated Food Frequency Questionnaire and Pregnancy Symptoms Questionnaire. Birth weight, birth length and head circumference were measured within 72 hours after delivery. Data were analysed using multiple linear regression adjusted for maternal height, prepregnancy body mass index, parity, gestational age at birth and neonatal gender. Among food groups, confectioneries was associated with lower birth weight (P=-l 00.36, P=0.028), head circumference (p=-0.47, P=0.025) and ponderal index (P=-0.84, P=0.024). Similarly, condiments showed a negative association with birth weight (P=-106.25, P=0.021) and head circumference (p—0.47, P=0.026) while tea and coffee intake was associated with higher head circumference to birth weight ratio (P=0.28, P=0.036). Among pregnancy symptoms categories, frequency of general symptoms showed a positive association with ponderal index (p=0.17, P=0.003) and severity of constitutional symptoms showed a negative association with birth length (p=-0.10, P=0.027). Comparison of food group intake across different pre-pregnancy BMI status (underweight, normal, overweight) was analysed using Kruskal-Wallis test. Among 11 food groups, beverage food group showed significant difference with P<0.01. These findings suggest that maternal dietary intake and pregnancy symptoms exert beneficial and adverse effects on foetal growth. Food selection and pregnancy symptoms management during pregnancy therefore will be important for long term health consequences of the child.